Особливості кристаломорфології топазу із камерних пегматитів Волині (за даними статистичних методів). - Вовк, Олександр Павлович; Наумко, Ігор Михайлович; Vovk, Oleksandr P.; Naumko, Ihor M. (Інститут геохімії, мінералогії та рудоутворення імені М. П. Семененка Національної академії наук України, 2014)
Volyn chamber pegmatites that are genetically and spatially related to granites of Korosten pluton located in the north-western part of the Ukrainian Shield are the only source of jeweler and technical topaz in Ukraine. The majority of topaz crystals in pegmatite bodies are found in chambers and leaching zones. Rarely topaz individuals are seen in cavities of the graphic, pegmatoid and feldspar zones and in metasomaticaly changed rocks, and also as hard inclusions in quartz. Topaz in Volyn chamber pegmatites, as the reliable typomophic mineral-indicator of acid-alkaline of fluid medium of the mineralogenesis, is precisely individualized crystallographically. We have studied 85 individuals and aggregates of topaz: 73 — from chamber areas and 12 from leaching zones. Statistical processing of goniometric research of crystals of Volyn topaz was conducted. Correlation was found between crystals size and their morphology. Morphologically important simple forms were determined according to general frequency, combination stability and relative development of faces. Morphology of crystals from different mineralogical-structural zones was compared. Six types of individuals were determined with the help of cluster analysis. Prisms of the vertical zone M {110} and l {120} are the main crystal forms of topaz. Faces f {011}, o {111}, u {112}, с {001} — y {021}, d {101}, X {023} are the most morphologically important on the heads of polyhedrons from chambers, according to the analysis of frequency and relative development of faces. Only three prisms M {110}, l {120} and f {011} are morphologically important in the leaching zone. Thus fre quency of the latter is higher than in the chambers. The bipyramids o {111}, u {112} and i {113} in the leaching zone, are found more often, than in the chambers, but due to their small sizes are not important to crystal habit. There is clear correlation between the sizes of individuals and their habit — on the large crystals we see more faces. An exception is made by the prism of f {011}, which is well developed on almost all individuals, regardless of size. The cluster analysis of morphology of 73 polyhedrons and aggregates from the chambers allowed distinguishing six types of crystals. Every type of crystals is typical of the individuals of defined size. Large crystals with reach habit can indicate the mineral forming conditions such as low growth rate and moderate supersaturation. The tables that allow defining morphological importance of every face depending on crystal sizes are attached.

За результатами дослідження 85 індивідів і зростків багатогранників топазу проведено статистичне опрацювання гоніометричних вимірювань їхніх кристалів із камерних пегматитів Волині. Виявлено кореляцію між розмірами кристала та його морфологією: на великих багатогранниках частота прояву більшості простих форм є вищою. Визначено морфологічно важливі прості форми із врахуванням загальної частоти, комбінаційної стійкості та відносного розвитку граней. Проаналізовано морфологію кристалів із різних мінералого-структурних зон пегматитових тіл. Найважливішими формами на індивідах топазу є призми вертикального поясу М {110} та l {120}. На головках багатогранників із заноришів найбільше розвинені f {011}, о {111}, u {112}, с {001}, y {021}, d {101}, X {023}. Кристалам із зон вилуговування властива бідніша огранка — на їхніх головках виявлено форми f {011}, о {111}, u {112}, с {001}, і {113}, d {101}, з яких добре розвинута лише перша. За допомогою кластерного аналізу встановлено шість морфологічних типів багатогранників. За наведеними таблицями можна визначити важливість кожної простої форми залежно від розмірів індивіду
Peculiarities of crystall morphology of topaz from chamber pegmatites of volyn according to data of statistical methods
Keywords: crystal morphology; goniometric measurements; topaz; chamber pegmatites; Volyn; statistics methods; кристаломорфологія; гоніометрія; топаз; камерні пегматити; Волинь; статистичні методи